Advanced Maternal Age‐associated SIRT1 Deficiency Compromises Trophoblast Epithelial−Mesenchymal Transition through an Increase in Vimentin Acetylation - Xiong, Liling; Ye, Xuan; Chen, Zhi; Fu, Huijia; Li, Sisi; Xu, Ping; Yu, Jiaxiao; Wen, Li; Gao, Rufei; Fu, Yong; Qi, Hongbo; Kilby, Mark D.; et al. (Aging cell, 2021)
Advanced maternal age (AMA) pregnancies are rapidly increasing and are associated with aberrant trophoblast cell function, poor placentation, and unfavorable pregnancy outcomes, presumably due to premature placental senescence. SIRT1 is an NAD+‐dependent deacetylase with well‐known antiaging effects, but its connection with placental senescence is unreported. In this study, human term placentas and first‐trimester villi were collected from AMA and normal pregnancies, and a mouse AMA model was established by cross breeding young and aged male and female C57 mice. SIRT1 expression and activity in HTR8/SVneo cells were genetically or pharmacologically manipulated. Trophoblast‐specific Sirt1‐knockout (KO) mouse placentas were generated by mating Elf5‐Cre and Sirt1fl/fl mice. Trophoblast cell mobility was assessed with transwell invasion and wound‐healing assays. SIRT1‐binding proteins in HTR8/SVneo cells and human placental tissue were identified by mass spectrometry. We identified SIRT1 as the only differentially expressed sirtuin between AMA and normal placentas. It is downregulated in AMA placentas early in the placental life cycle and is barely impacted by paternal age. SIRT1 loss upregulates P53 acetylation and P21 expression and impairs trophoblast invasion and migration. Sirt1‐KO mouse placentas exhibit senescence markers and morphological disruption, along with decreased fetal weight. In trophoblasts, SIRT1 interacts with vimentin, regulating its acetylation. In conclusion, SIRT1 promotes trophoblast epithelial−mesenchymal transition (EMT) to enhance invasiveness by modulating vimentin acetylation. AMA placentas are associated with premature senescence during placentation due to SIRT1 loss. Therefore, SIRT1 may be an antiaging therapeutic target for improving placental development and perinatal outcomes in AMA pregnancies. Both the first‐trimester villi and full‐term placentas from pregnancies of advanced maternal age (AMA) are associated with the significant downregulation of SIRT1 and accumulation of P53, P21, and β‐galactosidase in trophoblasts, where SIRT1 directly interacts with vimentin and modulates the acetylation status of vimentin, thus affecting the EMT process and ultimately influencing the invasiveness and mobility of trophoblasts. Both P53–P21 axis‐dependent cellular senescence and vimentin acetylation‐induced EMT suppression may orchestrate premature placental senescence and eventually lead to a variety of adverse pregnancy outcomes.